Enhancement of Inventory Management System of State Universities and Colleges in Mountain Province - Ayochok, Jona; Perez, Candido (PT FORMOSA CENDEKIA GLOBAL, 2024)
This qualitative research critically investigates the inventory management systems utilized by State Universities and Colleges (SUCs) in Mountain Province, revealing a significant gap in operational efficiency due to outdated processes and technologies. Employing a descriptive research design, the study systematically evaluates the limitations and challenges within the current framework of the Supply and Property Management Office (SPMO). The analysis uncovers substantial inefficiencies caused by manual procedures and obsolete technological tools, which hinder the institution's ability to effectively manage and allocate resources. The research identifies the urgent need for a modernized approach, advocating for integrating advanced digital technologies to optimize procurement, inventory tracking, and resource distribution. The proposed interventions aim to minimize errors, reduce operational delays, and enhance overall cost-efficiency, resulting in a more responsive and sustainable inventory management system tailored to the evolving needs of SUCs.